The Role Of External Auditing In The Administrative Reform Process In Syria - حركوك, هُمام; عمار , قصي (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This research aims to determine the relationship between external scrutiny and the administrative reform process in the Syrian Telecom Company (Lattakia branch). To achieve this objective, the researcher used a hypothetical-deductive approach to formulate the hypotheses. (55) questionnaires were distributed to the employees that are under study. (54) questionnaires were retrieved and (49) were valid for analysis. a statistical study was conducted to reveal this relationship. The researcher used the correlation coefficient (Person). The study concluded that there is a significant relationship between external scrutiny mechanism and the management reform process in the Syrian Telecommunications Company, Lattakia branch. This study also reached a set of recommendations and proposals, which would contribute positively in improving the administrative reform